Playing with phyre - "Marks, Graham" (London: Catnip, 2010)
"When everything Haden Akatine has ever known is obliterated by the ruthless Sadar, all he seeks is vengeance. What he finds is a conspiracy stretching across the Territories, to the Sadar's mountain stronghold, Ghadra. Here, in the heart of evil, a mysterious scheming sciencer is about to unleash Phyre - an explosive so deadly even he has no idea what will happen. Haden's quest is no longer one of revenge, it's one of survival"--Back cover
Donated from "Book Planet", Dated 18-4-2025.
Keywords: Science fiction